Treatment and Outcome of Patients with Skull Base Chordoma: A Meta-analysis - Amit, Moran; Na'ara, Shorook; Binenbaum, Yoav; Billan, Salem; Sviri, Gil; Cohen, Jacob T.; Gil, Ziv (Journal of Neurological Surgery Part B: Skull Base, 2014)
Objective Chordoma is a locally aggressive tumor. The aim of this study was to assess the efficacy of different surgical approaches and adjuvant radiation modalities used to treat these patients.Design Meta-analysis.Main Outcome Measures Overall survival (OS), disease-specific survival (DSS), and progression-free survival (PFS).Results The 5-year OS and PFS rates of the whole cohort (n = 467) were 86% and 65.7%, respectively. The 5-year DSS for patients who underwent open surgery and endoscopic surgery was 45% and 49%, respectively (p = 0.8); PFS was 94% and 79%, respectively (p = 0.11). The 5-year OS of patients treated with surgery followed by adjuvant radiotherapy was 90% compared with 70% of those treated by surgery alone (p = 0.24). Patients undergoing partial resection without adjuvant radiotherapy had a 5-year OS of 41% and a DSS of 45%, significantly lower than in the total-resection group (p = 0.0002 and p = 0.01, respectively). The complication rates were similar in the open and endoscopic groups.Conclusions Patients undergoing total resection have the best outcome; adjuvant radiation therapy improves the survival of patients undergoing partial resection. In view of the advantages of minimally invasive techniques, endoscopic surgery appears an appropriate surgical approach for this disease.
Keywords: skull base; chordoma; adjuvant; meta-analysis endoscopic